2021
DOI: 10.1080/19490976.2021.1892441
|View full text |Cite
|
Sign up to set email alerts
|

Mucin degrader Akkermansia muciniphila accelerates intestinal stem cell-mediated epithelial development

Abstract: Mucin-degrading bacteria are densely populated in the intestinal epithelium; however, their interaction with intestinal stem cells (ISCs) and their progeny have not been elucidated. To determine whether mucin-degrading bacteria play a role in gut homeostasis, mice were treated with Akkermansia muciniphila, a specialized species that degrades mucin. Administration of A. muciniphila for 4 weeks accelerated the proliferation of Lgr5 + ISCs and promoted the differentiation of Paneth cells and goblet cells in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
116
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(119 citation statements)
references
References 68 publications
3
116
0
Order By: Relevance
“…This idea is strongly supported by our results of A. muciniphila intervention experiments, showing an enhanced resistance to Citrobacter infection and intestinal inflammation in mice inoculated with A. muciniphila. A. muciniphila , a gram-negative and strictly anaerobic bacterium, is the only cultivated intestinal representative of the phylum Verrucomicrobia 28 and has been implicated in gut barrier function, immune response, and host metabolism 29 , 30 . Notably, it has been suggested that reduced levels of A. muciniphila have been observed in patients with obesity, 31 diabetes, 32 metabolic disorders, 33 and inflammatory bowel diseases (mainly ulcerative colitis), 34 which suggests it may have potential role to play in regulating host functions, anti-inflammatory properties and protection against enteropathogenic bacteria infection.…”
Section: Discussionmentioning
confidence: 99%
“…This idea is strongly supported by our results of A. muciniphila intervention experiments, showing an enhanced resistance to Citrobacter infection and intestinal inflammation in mice inoculated with A. muciniphila. A. muciniphila , a gram-negative and strictly anaerobic bacterium, is the only cultivated intestinal representative of the phylum Verrucomicrobia 28 and has been implicated in gut barrier function, immune response, and host metabolism 29 , 30 . Notably, it has been suggested that reduced levels of A. muciniphila have been observed in patients with obesity, 31 diabetes, 32 metabolic disorders, 33 and inflammatory bowel diseases (mainly ulcerative colitis), 34 which suggests it may have potential role to play in regulating host functions, anti-inflammatory properties and protection against enteropathogenic bacteria infection.…”
Section: Discussionmentioning
confidence: 99%
“… Akkermansia muciniphila is a mucin-degrading specialist that colonizes the mucus layer of the human gastrointestinal tract ( 1 ). Paradoxically, Akkermansia also promotes mucus production by enhancing the differentiation of gut epithelial cells, thereby influencing mucosal homeostasis ( 2 ). Numerous positive associations have been observed between this bacterial lineage and human health.…”
Section: Introductionmentioning
confidence: 99%
“…Lactobacillus as well-known probiotics have been proved to be associated with improvement in patients suffering from radiation syndrome in clinical trials ( Linn et al, 2019 ). A recent study has reported that A. muciniphila improves intestinal radiation injury following whole body irradiation ( Kim et al, 2021 ). Notably, the experimental mice in the present study were exposed to abdominal local irradiation, which is more similar to iatrogenic irradiation such as radiotherapy for pelvic and abdominal tumors.…”
Section: Discussionmentioning
confidence: 99%